Tenement House "Pod Kruki", Market Square 25, Krakow. The Present of History – the Layering of the Future - Włodarczyk, Marcin; Włodarczyk, Małgorzata Mariola (Protection of Cultural Heritage, 2021)
Architecture is the art of building, that is, gathering durable materials and agglomerating them in such a way as to produce a work that is durable, functional, and beautiful (as described by the Vitruvian triad: firmitas, utilitas, venustas). The completion of construction marks the beginning of the building's duration. The duration of architecture almost always involves making changes. It would be wonderful to let architecture last indefinitely, with its original shapes, textures, and materials preserved. Technical progress, changes in needs, natural and historical accidents, and many other factors make it necessary to introduce changes in the object. Persistence of architecture is a constant change and it is good if they are created by EVOLUTION. Layering is like writing a book, page by page. It then allows you to "read" the architecture and with it the history of the place and the people. Layering is more interesting than exchanging. The loss in the case of replacement is that the previous stage that was removed, whether by disaster or intentionally, is like a page torn out of a book. A modern intervention in a historic building must respect the previous pages, the previous layering. Sometimes it can even fill in some missing pages or rather point them out. The wise course of action in such a case is not guided only by the orders of conservation services. Empathy for architectural/book records is a challenge for creators, especially architects. We will show such a process on the example of the tenement house number 25 Market Square in Krakow, which is an example of careful modernization of structure and space while preserving legible traces. It is also a nod of the present to the future of the new spirit of this space.